Língua portuguesa e ludicidade: ensinar brincando não é brincar de ensinar - Almeida, Paulo Nunes de (2007)
This study presents a panorama of the use of ludic activities in the Portuguese language teaching and learning and emphasizes the use of games and plays at school in order to improve children s knowledge about their mother tongue and their roles in society. In order to achieve its goals, it presents the origins of the word ludic, its historical aspects and the Process of Cognitive Development formulated by Piaget. It also presents some ludic activities to be used at school to facilitate the Portuguese language teaching in a way children effectively learn school subjects and feel comfortable and motivated to learn. As a theoretical feature, this study is based on de Brougère (2002), Brunner (1974, 1977, 1986 and 2001), Chateau (1987), Freire (1977, 1983 and 1989), Piaget (1973 and 1990), Piaget & Inhelder (1974 and 1968), Snyders (1974, 1988 and 1993), Vygotsky (1987, 2000 and 2001)